The role of the pharmacist in identifying and solving drug-related problems: an integrative review (Research, Society and Development, 2022)
Objective: to develop an integrative review of the role of the pharmacist in identifying and solving problems related to medications, with the aim of creating and conducting techniques that intend to improve the safe use of drugs and favoring the population's quality of life. Methods: concerns an integrative literature review on the role of pharmacists in identifying and solving drug-related problems. Results: medication failures are a global public health problem, as in addition to the harm caused to the patient's health, they produce an increase in hospital stays, increase in health costs, and contribute to the financial barriers directed at this sector. For the most part, errors are preventable and can be performed by both new and experienced professionals, whether doctors, pharmacists, nurses, technicians, caregivers, and the patient. Conclusion: The pharmacist is a substantial professional in the health team assigned to the care of patients who are using medication, having to act in an integrated manner with other professionals, with the sole objective of enabling health and sustaining an effective treatment for the patient. The professional is one of the last possibilities to discern, repair or limit probable risks associated with the therapy.